Optimization of Early Detection of Growth and Motor Development in Preschool Children Using the DDST and KPSP Methods at KB As-Salamah Peterongan, Jombang - Wulandari, Dewi Triloka; Azizah, Ninik; Rahmawati, Vivin Eka; Annuchasary, Helmi (Indonesia Berdaya, 2024)
Early age is the age of 0-8 years which is the age in the golden age of a child. At this time, all potentials at this age must be developed comprehensively in terms of cognitive, language, social-emotional, and physical motor. With regard to its potential in motor physical development, early childhood has high energy. This energy is needed to carry out various activities necessary to improve physical skills, both related to improving gross motor and fine motor skills. Physical activity and the release of large amounts of energy are characteristic of children's activities during this period. This is because the energy possessed by children in large quantities requires distribution through various physical activities, both physical activities related to gross motor movements and fine motor movements. The purpose of this community service activity is to detect early childhood delays or deviations in development. This community service was held at KB As Salamah Peterongan Jombang on November 12, 2024. The approach used is to screen children's growth and development using DDST and KPSP sheets as an effort to detect early delays in child development. The procedure for implementing activities is divided into three stages, namely the preparation stage, the implementation stage, and the evaluation and monitoring stage. The method used is question and answer by the target. The media used are game props and DDST and KPSP sheets and Height and Weight Measuring Instruments that provide convenience in developing materials and facilitate the explanation of the material. Educational participants were 10 children at KB As Salamah Peterongan Jombang to conduct growth and development screening examinations. The result of community service activities is that it is known that no child has a risk of delay in growth and development, and the growth and development of children is in accordance with their age